PENGARUH PERAWATAN PRASARANA, SARANA, DAN UTILITAS TERHADAP KEPUASAN PENGHUNI PADA KAWASAN PERUMAHAN DI SURABAYA - Njo Anastasia; Timoticin Kwanda; Dicky Fredy Widjaja (Tesa Arsitektur, 2018)
Developers undertake construction and maintenance of public facilities, social facilities including infrastructure, facilities and utilities in housing estate. The purpose of the maintenance is to increase the value of housing and to comfort the residents. This study aims to identify and evaluate the influence of the types of maintenance undertaken by the developers on the satisfaction of the residents.Data were obtained by distributing questionnaires to housing residents in Surabaya who have lived at least 1 (one) year. The surveyed housing estate has an Environmental Management Agency.The number of respondents obtained are about 100 people with convenience sampling technique.Data processing using SEM-PLS and Kendall’s way analysis of non-parametric test. The results showed that residents of housing estate in Surabaya were satisfied with the maintenance done by the developer. The three types of maintenance that have been performed byEnvironmental Management Agencyare considered good by residents, including corrective maintenance, routine maintenance, and cosmetic maintenance. Furthermore, residents of housing in West Surabaya even showed a higher level of satisfaction with the maintenance done by each BPL than residents in East Surabaya and South Surabaya